A Quadratic Non-Isolated High Step-Up Single-Input Dual-Output DC–DC Topology Based on Coupled Inductors with Low Input Current Ripple - Vafa Marzang; Shirazul Islam; Sina Ahmadian; Atif Iqbal; Hasan Mehrjerdi; Dong Cao; Shuo Wang (IEEE Open Journal of Power Electronics)
This paper presents a new flexible high step-up DC-DC converter based on coupled inductors (CI), which operates as a Single-Input Dual-Output (SIDO) or Single-Input Single-Output (SISO) converter. The proposed SIDO (or SISO) topology includes two CI, two independent switches, four (three) diodes, and five (four) capacitors. The proposed converter produces high DC output voltages at a low value of duty cycles and low voltage stress across the power MOSFETs. The CIs’ turn ratios give another freedom factor to increase the output voltages and decrease the switches’ stress. The proposed converter ensures low input current ripple by designing the first coupled inductor’s turn ratios. The converter’s operation is analyzed at three zones of the switches’ duty cycles, and the optimum zone is detected to enhance the converter’s efficiency. Dynamic modeling, control strategy, and decoupling of dual output topology are thoroughly investigated. A comparison of the proposed converter with other SIDO/SISO topologies reported in the literature is provided, and the critical features of the proposed converter are highlighted. Finally, these features are proven based on a prototype at power rating and switching frequency of 500 W and 50 kHz, in which the highest efficiency is measured at 200 W and equals 96.4%.